Manggaleh Culture-Based Experiential Learning in Social Entrepreneurship Education: A Preliminary Study in Social Studies Education - Cicilia Melinda; Bunyamin Maftuh; Kokom Komalasari; Acep Supriadi; Wisal Jereis Asad Alrabadi (Yayasan Keluarga Guru Mandiri, 2026)
This study examines entrepreneurship education in the social studies education program, highlighting the limited integration of original socio-artistic surrounds in current practice. Approaches remain generally theoretical and techno-economic, leading to the underdevelopment of socio-entrepreneurial chops, particularly in social creativity and real-world problem solving. This study aims to dissect current literacy conditions and assess West Sumatra. A mixed-methods primary design was employed, involving compliance, semi-structured interviews, document analysis, and a questionnaire administered to lecturers and students from two universities. Data were analyzed using descriptive, qualitative, and quantitative approaches. The findings reveal a gap between lecturers' social exposure and students' profitable exposure, alongside dominant practices with minimal artistic integration. Although overall socio-entrepreneurial chops were fairly high (M=4.19), skills were linked to social perceptivity and invention (M=3.68). This study offers a culturally predicated Experiential learning frame grounded in Manggaleh values, furnishing a contextually applicable approach to bridging proposition and practice in socioentrepreneurship education.